Obstructive jaundice induces early depression of mitochondrial respiration in rat hepatocytes - Younes,Riad Naim (2007)
INTRODUCTION: Oxidative phosphorylation dysfunction of hepatocyte mitochondria is involved in the pathophysiology of organ dysfunction following obstructive jaundice (OJ). However the time period from biliary occlusion to the occurrence of the dysfunction has not been determined decisively. PURPOSE: To evaluate the early effects (1 d and 7 d) of OJ on liver mitochondria respiratory function in rats. METHODS: Male Wistar rats (200-250 g) were randomly divided into the following 3 groups: laparotomy plus OJ for 24 h (1d group) (n = 10); laparotomy plus OJ for 7 d (7d group) (n = 10); sham control procedure (CTR group) (n = 12). At the end of OJ periods, total serum bilirubin level, hepatic enzyme activity levels (GOT, GTP, Gama-GT, ALP), mitochondrial respiration phases S3 and S4, as well as the respiratory control ratio (RC = S3/S4), and ADP consumption/oxygen consumption (ADP/O) ratio, were determined. RESULTS: Total serum bilirubin, activity of most hepatic enzymes, and O2 consumption during basal (S4) respiration were increased in the 1d and 7d groups (ANOVA, p = 0.05 vs. CTR). After ADP addition, the O2 consumption rate (S3) in the 1d group remained similar to the CTR rate (ANOVA p > .05), while the RC rate was reduced (ANOVA, p = 0.001) vs. CTR. The effects observed on mitochondrial respiration in the 1d group were exacerbated in the 7d group. CONCLUSION: These results indicate that OJ induces early (24 h) depression of liver mitochondria respiration, and thus may lead to early reduction in the production of high energy bonds.